Associations between seminal plasma osteopontin level and sperm motility in infertile men with asthenozoospermia - Zhang, Peng; Leng, Yifu; Liu, Yuanxin; Liu, Jiayi; Li, Chaoran; Qin, Jie (Frontiers in Endocrinology, 2025)
PurposeMale infertility, a complex multifactorial condition, is frequently caused by asthenozoospermia (AZS). Although osteopontin (OPN) has been implicated in mammalian reproduction, its specific effects on sperm motility and fertility are not well understood. This study investigates the relationships between seminal plasma OPN levels and sperm parameters in cases of male infertility.MethodsA total of 158 semen samples were analyzed, comprising 78 from infertile men with AZS and 80 from healthy fertile controls. OPN concentrations in seminal plasma were measured using the ELISA method. Additionally, we assessed the in vitro effect of OPN on sperm motility parameters in AZS patients and controls.ResultsSignificantly lower OPN concentrations were observed in the seminal plasma of infertile men with AZS compared to healthy controls (P<0.0001). OPN levels discriminated between the groups, with an area under the curve of 0.793. Additionally, in vitro OPN treatment significantly improved sperm motility in the AZS group, enhancing progressive and total motility, as well as kinematic parameters in a concentration-dependent manner.ConclusionsThis study established a link between OPN level and sperm motility in infertile individuals with AZS, suggesting the potential of OPN as a biomarker for AZS and as a supplement for assisted reproductive techniques.